Analysis of Islamic Business Ethics Related to Return of Remaining Prices in Kind (Case Study of Taraju Tasikmalaya Market) - Ranti Ismayanti (CV. Rayyan Dwi Bharata, 2022)
The problem in this study is the Return of Remaining Prices in the Form of Goods at the Tasikmalaya Taraju Market and what are the factors causing the practice. This study